Behavioral Differences of Laying Hens with Fractured Keel Bones within Furnished Cages - Casey-Trott, Teresa M.; Widowski, Tina M. (Frontiers in Veterinary Science, 2016)
High prevalence of keel bone fractures in laying hens is reported in all housing systems. Keel fractures have been associated with pain and restricted mobility in hens in loose housing. The objective was to determine whether keel fractures were associated with activity of hens in furnished cages. Thirty-six pairs of LSL Lite hens (72 wk) were enrolled in the study. One hen with a fractured keel and one hen without were identified by palpation in each of 36 groups of hens housed in either 30 or 60-bird cages stocked at 750cm2/hen. Behavioral activity of each hen was recorded by four observers blind to keel status using focal animal sampling for 10 min within a 2 hr period in the morning (08:00-10:00), afternoon (12:00-14:00), and evening (17:00-19:00). All hens were observed during each of the three sample periods for three days totaling 90 min, and individual hen data was summed for analysis. Hens were euthanized 48hr after final observations, dissected, and classified by keel status: F0 (no fracture, N=24); F1 (single fracture, N=17); F2 (multiple fractures, N=31). The percentages of time hens performed each behavior were analyzed using a mixed procedure in SAS with fracture severity, body weight, cage size, rearing environment, and tier in the model. Fracture severity affected the duration of perching (P=0.04) and standing (P=0.001), bout length of standing (P<0.0001), and location (floor vs perch) of resting behaviors (P=0.01). F2 hens perched longer than F0 hens, 20.0% ± 2.9 and 11.6% ± 3.2. F2 hens spent less time standing, 15.2% ± 1.5, than F0 and F1 hens, 20.7% ± 1.6 and 21.6% ± 1.8. F2 hens had shorter standing bouts (22.0 sec ± 4.2) than both F0 and F1 hens, 33.1 sec ± 4.3 and 27.4 sec ± 4.4. Non-fractured hens spent 80.0% ± 6.9 of total resting time on the floor whereas F1 and F2 hens spent 56.9% ± 12.4 and 51.5% ± 7.7, resting on the floor. Behavioral differences reported here provide insight into possible causes of keel damage, or alternatively, indicate a coping strategy used to offset pain or restricted mobility caused by keel fractures.